1981
DOI: 10.1007/bf02409493
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the orientation and particle size of the mineral phase in human femoral cortical bone

Abstract: It has previously been observed that after the third decade of life the tensile strength of bone decreases faster than its density [1], indicating that some microstructural change occurs in bone with advancing age. In order to try to elucidate this observation, the orientation and particle size of the mineral phase of bone have been studied with respect to age. Samples were taken from femora varying in age from 13 to 97 years. The results show that the degree of preferred orientation does not vary with age aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 22 publications
3
30
0
2
Order By: Relevance
“…Previous studies have shown the solubility of apatite increases as the lattice microstrain is increased [71]. Further, disorder within the apatite lattice, has been proposed as a fundamental contributor to bone mechanical compromise for more than three decades [65]. In this study, with increasing coherence length values, increases in TbTh, TMD and BV/TV were observed.…”
Section: Architecturesupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have shown the solubility of apatite increases as the lattice microstrain is increased [71]. Further, disorder within the apatite lattice, has been proposed as a fundamental contributor to bone mechanical compromise for more than three decades [65]. In this study, with increasing coherence length values, increases in TbTh, TMD and BV/TV were observed.…”
Section: Architecturesupporting
confidence: 52%
“…Previous studies have suggested that crystal size is related to mechanical strength [65 -67], and that increased bone mineral crystal size is associated with increased bone fragility [65]. However, after reporting a decrease in crystal thickness with age as crystal length increases, Boskey and Mendelson suggested from their preliminary data that mechanical strength is greater when the average crystallinity is greater [68].…”
Section: Xrd: Crystallinitymentioning
confidence: 99%
“…This is in agreement with our recent report [10] that collagen maturity is also greatest in the highturnover cases, again indicating that this is the oldest bone. Larger crystals, decreased collagen flexibility (associated with increased cross-linking) and decreased mineral content are qualities of bone that are time-dependent, changing in relation to the age and "maturity" of the deposited matrix, and all play a role in making the bone more fragile [5,21]. We speculate that the differences between samples from normal individuals and from cases of both types of osteoporosis can be explained by the variations in the rates of formation and resorption apparent in the normal and abnormal biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the material properties that must be considered are the amount and characteristics of both the organic matrix and the mineral [2,3,4,5]. Fourier transform infrared microspectroscopy (FTIRM) and infrared imaging (FTIRI) have been used to characterize the changes that occur in the mineral and matrix components of iliac crest biopsies obtained from post-menopausal osteoporotic woman and normal controls [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…88 To achieve adequate mechanical properties, larger crystals had an increased requirement for perfection. Crystal size grows with tissue aging 89 sometimes spectacularly in hip fracture cases. 90 Osteocytes may also function collectively as a syncytium: 91 they are sensitive to mechanical loading, promote 65 bone breakdown and regulate its growth, 66 may locally regulate matrix mineralisation 92 and also mobilise calcium 63,93 in response to PTH signalling.…”
Section: Osteocytes: Additional Regulatory Roles?mentioning
confidence: 99%